(untitled) (Journal of Philosophy Culture and Political Science, 2019)
The significant frequency of conflicts and acuteness of the problems ensued necessitates detection of the real causes and meaningful study of the social consequences. This in turn necessitates study of conflict formation patterns under the science of conflictology. Therefore, of special importance are the establishment of conflictology in Kazakhstan and the process of its institutionalization as a science. The author’s main purpose is an attempt to represent major features of the conflict reviewed from the perspective of its positive and negative properties. The author pays attention to conflict problematization in Kazakhstan. Materials and methods: The methodological basis of this research is the scientific and historic paradigm of conflict analysis, which proposes to consider a conflict not only in its theoretical aspect but also in the aspect of the society’s historic development.Research results: It is substantiated that conflictology is related to mediation actualization as an alternative method of conflict resolution. The main phases of conflictology development in the USSR and Kazakhstan are distinguished. Discussion and conclusion: The analysis marks the problems that thwart development of conflictology in Kazakhstan, the problems of conceptual nomenclature and opportunities for conflict settlement. The key areas of conflictology are described in conflict resolution and conflict possibility reduction. The research ascertains that a clear differentiation between mediation and conflictology is required to clearly define the conflictological content. According to the author, conflictology should be promoted based on the systematized knowledge of conflict and post-conflict negotiations technologies development. Key words: conflict; mediation, negotiations technologies; society.